ChemInform Abstract: Cobalt(III)‐Catalyzed Directed C—H Coupling with Diazo Compounds: Straightforward Access Towards Extended π‐Systems. Issue 32 (August 2015) - Zhao, Dongbing; Kim, Ju Hyun; Stegemann, Linda; Strassert, Cristian A.; Glorius, Frank
Abstract For the first time, an efficient and scalable cobalt‐catalyzed directed C—H functionalization with carbene precursors is presented.